Coffee : emerging health effects and disease prevention - Chu, Yi-Fang; Institute of Food Technologists (Ames, Iowa : IFT Press, Wiley-Blackwell, A John Wiley & Sons, Ltd., Publication, 2012)
Coffee: Emerging Health Benefits and Disease Prevention presents a comprehensive overview of the recent scientific advances in the field. The book focuses on the following topics: coffee constituents; pro- and antioxidant properties of coffee constituents; bioavailability of coffee constituents; health benefits and disease prevention effects of coffee; and potential negative impacts on health. Multiple chapters describe coffee's positive impact on health and various diseases: type 2 diabetes; neurodegenerative diseases (Parkinson's and Alzheimer's); cancer (prostate, bladder, pancreatic, breast.
Includes bibliographical references and index.
Print version record.
Keywords: Coffee -- Health aspects; Caffeine -- Physiological effect; Coffee -- physiology; Coffee; Agriculture; Science; Natural history; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; Caffeine -- Physiological effect; Coffee -- Health aspects; Electronic books